Karakteristik Perusahaan dan Pemilihan Kebijakan Akuntansi - Adilla Khairina; Nova Novita (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2020)
This research focuses on the relationship between firm characteristics and the choice of accounting policies by examining their accounting-policy disclosure Agroindustrial companies registered in Southeast Asia are represented by Malaysia, Thailand and Indonesia. This research uses positive accounting theory and agency theory. The research investigates managers’ decisions related to accounting methods using panel data from the year 2014-2018. This study uses a sample of Agro-industry companies in 3 countries in ASEAN during the 2014-2018 period.Thirty companies listed on Bursa Malaysia, Stock Exchange of Thailand and Bursa Efek Indonesia were analyzed by using random-effect model. The result shows that financial leverage and ownership concentration are significant determinants of accounting policy choice. However, this paper did not find a significant relationship between accounting policy choices and profitability, firm size, investment opportunity set, and assets-in-place. The results of the study were also influenced by global commodity market that is experiencing a decline in the last three years. Keywords:   ASEAN; Accounting Policy Choices; Firm Characteristics; Income; Agroindustry; Earnings Management